Metode Analisis Akar Masalah dan Solusi - P., Ari Harsono (Makara Human Behavior Studies in Asia, 2008)
Most of discourses in meetings, discussions, conferences and talk shows are not equipped with a method which analyzes the root cause and its fundamental solution, and even without the need of analyzing it. As the result,. the discourses almost never find the root cause, and so automatically there are be no fundamental solution. The Method of Root Cause Analysis and Solutions (MRCAS) gives a mode of thought figured by a flow chart and some examples. Application of MRCAS helps its users simultanously thinking inductively and deductively, qualitatively and quantitatively, more deeply and holistically, and also facilitate them in inter or multi or transdiscipline cooperation.